Social communication and inclusive teaching practices: an action research case study - Makoelle, T. M. (Department of Communication Science, University of the Free State, 2012)
This article reports on how social communication was used to enhance a network for the development of inclusive teaching practices within the framework of an action research project. A team of 15 teachers at a Free State school embarked on action research to reflect on the inclusive practice in relation to inclusive teaching and learning with a view of improving their inclusive teaching skills. Data was collected using discussions, observations, field notes, and focus group interviews. Several communication platforms were created by the group to advance this ideal and to share information, namely Facebook, mobile communication (SMS/MMS), teleconferences, meeting of the community of enquiry, brainstorming meetings, discussions, use of diaries, and group interpretative engagements. Among the findings of the study is that social communication via social media as discourse has created an appropriate platform for coherent and empowering engagement about developing inclusive teaching practices and has resulted in a sustained learning environment. The social communication network provided a framework for reflection on practice resulting in the change of attitudes and improved inclusive pedagogy.
Keywords: Teaching; Networks; Social communication; Communication platforms; South Africa; Free State